Fracture Resistance of Endodontically Treated Teeth Restored with Fiber-Reinforced and Stress-Decreasing Composites: A Comparative In-Vitro Analysis - Karale, Amruta Tushar; Lakade, Laxmi; Shah, Preetam; Choudhary, Shweta; Jajoo, Shweta; Patil, Krishna (Journal of Neonatal Surgery, 2025)
Background: Endodontically treated teeth often suffer from diminished fracture resistance due to structural alterations such as moisture loss, dentin dehydration, and access cavity preparation. Selecting suitable core build-up materials is crucial for restoring their strength and ensuring long-term functionality. Objective: This study aimed to compare the fracture resistance of endodontically treated premolars restored with fiber-reinforced composite (GC EverX Flow) and stress-decreasing resin composite (Dentsply SDR), using both occlusal and mesio-occluso-distal (MOD) cavity preparations. Methodology: Forty-nine freshly extracted maxillary premolars were divided into seven groups based on cavity design and restorative material. After standardized endodontic treatment, core build-up was done using either GC EverX Flow or SDR. Fracture resistance testing was performed using a universal testing machine, and data were analysed using ANOVA and post hoc comparisons. Results: The highest mean fracture resistance was observed in the control group (721.14 N), followed by Dentsply SDR in MOD preparations (613.21 N), and GC EverX Flow in MOD (583.86 N). MOD groups with no restorative material showed the lowest resistance (337.29 N). Statistical analysis confirmed that both GC EverX and SDR composites significantly enhanced fracture resistance compared to unrestored controls, especially in MOD cavities. Conclusion: Fiber-reinforced and stress-decreasing composites effectively reinforce endodontically treated teeth, especially in structurally compromised MOD designs. SDR exhibited slightly superior performance, suggesting its clinical advantage in restoring weakened teeth. These findings guide clinicians in selecting optimal restorative materials to enhance durability and reduce the risk of post-treatment fracture.